1997
DOI: 10.1901/jaba.1997.30-485
|View full text |Cite
|
Sign up to set email alerts
|

A Response‐restriction Analysis of Stereotypy in Adolescents With Mental Retardation: Implications for Applied Behavior Analysis

Abstract: The behavior of 4 adolescents with severe or profound mental retardation was evaluated in the presence of four sets of materials during periods of unstructured leisure activity. Functional engagement with the materials, stereotypic engagement with the materials, stereotypy without interaction with the materials, and other aberrant behaviors were recorded. Across a series of experimental conditions, the number of sets of materials was reduced from four to one by eliminating the set most frequently manipulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Koegel et al suggested that the results reflected response covariation in which altered consequences for one response affected the probability of another response. Results obtained in both the Koegel et al study and the present study also are consistent with those reported by McEntee and Saunders (1997), who showed that when one stereotypic response was restricted by removing relevant materials, individuals simply reallocated their responding to other materials.…”
Section: Discussionsupporting
confidence: 93%
“…Koegel et al suggested that the results reflected response covariation in which altered consequences for one response affected the probability of another response. Results obtained in both the Koegel et al study and the present study also are consistent with those reported by McEntee and Saunders (1997), who showed that when one stereotypic response was restricted by removing relevant materials, individuals simply reallocated their responding to other materials.…”
Section: Discussionsupporting
confidence: 93%
“…Neither Green and Striefel (1988) nor McEntee and Saunders (1997) reported the total number of sessions conducted or the total RR assessment time for each participant; therefore, it is not possible to compare the efficiency of the assessments, given previously described restriction rules and those used in the current study. However, the rules used in the current study allowed items to be removed following two (rather than a minimum of four) sessions, and a condition was never conducted for more than seven sessions (a 10-session criterion was often used in the Green & Striefel and McEntee & Saunders studies).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently repeating the assessment after removing the most preferred activity from the pool of available items would overcome problems associated with exclusive preference. Responserestriction (RR) analyses of this type have been used with both nonhumans (Lyons & Cheney, 1984) and humans (Bernstein & Ebbeson, 1978;Green & Striefel, 1988;McEntee & Saunders, 1997) to develop models that predict which of two or more alternative responses will emerge when other responses are restricted. The procedures differ along a number of dimensions, but all involve the measurement of response allocation among several concurrently available activities under conditions in which responding is progressively restricted to fewer and fewer options.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because stereotypy may occur at high rates during unstructured time (McEntee & Saunders, 1997), interventions that reduce stereotypy during free time are an important part of effective programming for children with autism. Effective interventions for vocal stereotypy in individuals with developmental disabilities include differential reinforcement (e.g., Taylor, Hoch, & Weissman, 2005), response interruption and redirection (e.g., Ahearn, Clark, MacDonald, & Chung, 2007), and noncontingent auditory stimulation.…”
mentioning
confidence: 99%